Clustering of water molecules in ultramicroporous carbon: In-situ small-angle neutron scattering. (January 2017) - Bahadur, J.; Contescu, C.I.; Rai, D.K.; Gallego, N.C.; Melnichenko, Y.B.
Abstract: The adsorption of water is central to most of the applications of microporous carbon as adsorbent material. We report early kinetics of water adsorption in ultramicroporous carbon using in-situ small-angle neutron scattering. It is observed that adsorption of water occurs via cluster formation. Interestingly, the cluster size remains constant throughout the adsorption process whereas the number density of clusters increases with time. The role of surface chemistry of microporous carbon on the early kinetics of adsorption process was also investigated. The present study provides direct experimental evidence for cluster assisted adsorption of water molecules in microporous carbon (Do-Do model).